2000
DOI: 10.1007/s001140050740
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic pattern processing

Abstract: A table-top prototype has been constructed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Ions not involved as reactants have in numerous cases been found to enhance enzymatic activity [300,301] and an activating effect has been found [302] for Mg 2+ (and exists according to our observations [297] also of Ca 2+ ) affecting MDH. On the other hand, high ionic strength unspecifically suppresses MDH activity [303].…”
Section: Conformation-based Computationsupporting
confidence: 77%
See 1 more Smart Citation
“…Ions not involved as reactants have in numerous cases been found to enhance enzymatic activity [300,301] and an activating effect has been found [302] for Mg 2+ (and exists according to our observations [297] also of Ca 2+ ) affecting MDH. On the other hand, high ionic strength unspecifically suppresses MDH activity [303].…”
Section: Conformation-based Computationsupporting
confidence: 77%
“…Therefore the catalytic activity of such enzymes provides a sensitive indicator of conformation change. Experimental studies with the enzyme malate dehydrogenase (MDH) showed that divalent ions can be used to modulate its activity [297]. If inputs are coded with ionic signals and the concentration of the product formed by the reaction catalyzed by MDH is regarded as the output signal a variety of logic gates (AND, OR, XOR, NAND, NOR) with a response time of less than 10 s have been implemented using Mg 2+ and Ca 2+ as input signals [298].…”
Section: Conformation-based Computationmentioning
confidence: 99%
“…Non-linear and non-monotonic responses in biological systems offer the possibility of implementing functions such as the XOR. Ross and co-workers demonstrated a simple enzymatic reaction scheme capable of implementing a biochemical XOR function (Hjelmfelt, Weinberger et al 1991;Arkin and Ross 1994) and Zauner and Conrad experimentally demonstrated an implementation of the XOR function by exploiting the nonmonotonic response of the mitochondrial malate dehydrogenase (mMDH) reaction rate to ion concentrations (Mg 2+ , Ca 2+ ) (Zauner and Conrad 2000).…”
Section: Structure Of the Modelmentioning
confidence: 99%
“…Shamayaev and G.Y. Peshkov, unpublished results), pattern recognition (Zauner and Conrad 2000) and universal logical computation Adamatzky 2001).…”
Section: Introductionmentioning
confidence: 99%